2007
DOI: 10.1080/13880200701214755
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocic Activity of Leaf Extract ofSpondias mombin.

Abstract: The oxytocic property of leaf extract of Spondias mombin Linn. (Anacardiaceae) was evaluated in relation to its folkloric use by traditional birth attendants. The abortifacient effect of the methanol leaf extract (ME) obtained by cold maceration for 48 h, was evaluated in vivo in pregnant mice and rats at different trimesters of pregnancy. The effect of ME on isolated gravid and nongravid rat uteri preparations as well as on spontaneous contractile frequency and amplitude were investigated in vitro. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Several biological activities of the plant have been reported, including antiviral, 21 23 antibacterial and mollus-cicidal, 15 , 23 β-lactamase inhibitory, 24 anti-inflammatory, 16 wound healing, 19 antipsychotic, anticonvulsant and sedative, 18 , 20 abortifacient, 11 oxytocic, 25 antimicrobial, 26 anti-fertility, 27 antigonadotrophic, 28 hematinic, 29 antioxidant, 30 antidiabetic 31 and anticholinesterase activities. 32 …”
Section: Introductionmentioning
confidence: 99%
“…Several biological activities of the plant have been reported, including antiviral, 21 23 antibacterial and mollus-cicidal, 15 , 23 β-lactamase inhibitory, 24 anti-inflammatory, 16 wound healing, 19 antipsychotic, anticonvulsant and sedative, 18 , 20 abortifacient, 11 oxytocic, 25 antimicrobial, 26 anti-fertility, 27 antigonadotrophic, 28 hematinic, 29 antioxidant, 30 antidiabetic 31 and anticholinesterase activities. 32 …”
Section: Introductionmentioning
confidence: 99%
“…The leaves have also been demonstrated to have antihelminthic (Ademola et al, 2005) and abortifacient (Offiah and Anyanwu, 1989;Nworu et al, 2007) properties. In traditional medical practice of southern Nigeria, the freshly boiled aqueous leaf extract of SM is used to treat dizziness, especially after childbirth, while the bark is used to treat mothers after delivery (Onwuka, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Some plants were reputed to have uterotonic effect and thus allowed calcium mobilization in order to induce uterine smooth muscle contraction. Among them, the fresh leaves of Spondias mombin were crushed and used traditionally in Togo by healers to treat dystocia and manage post-partum hemorrhage2 and to expel placenta in Nigeria3. In our previous study, we have shown that hydro-ethanolic extract of S. mombin leaves could contract uterus smooth muscle by cytosolic calcium rising.…”
Section: Introductionmentioning
confidence: 99%